Life in revolutionary France - Harder, Mette; Heuer, Jennifer Ngaire, 1969- (London, England : Zed Books, 2020)
"The French Revolution brought momentous political, social, and cultural change. 'Life in Revolutionary France' asks how these changes affected everyday lives, in urban and rural areas, and on an international scale. An international cast of distinguished academics and emerging scholars present new research on how people experienced and survived the revolutionary decade, with a particular focus on individual and collective agency as discovered through the archival record, material culture, and the history of emotions. It combines innovative work with student-friendly essays to offer fresh perspectives on topics such as: Political identities and activism; Gender, race, and sexuality; Transatlantic responses to war and revolution; Local and workplace surveillance and transparency; Prison communities and culture; Food, health, and radical medicine; Revolutionary childhoods. With an easy-to-navigate, three-part structure, illustrations and primary source excerpts, 'Life in Revolutionary France' is the essential text for approaching the experiences of those who lived through one of the most turbulent times in world history"--
Introduction: Rethinking the Revolutionary Everyday / Mette Harder and Jennifer Ngaire Heuer -- Part 1: Revolutionary Identities and Spaces : 1. Republicans and Royalists: Seeking Authentic Rural Voices in the Sources of the French Revolution / Jill Maciak Walshaw -- 2. Mapping Women's Everyday Lives in Revolutionary Marseille / Laura Talamante -- 3. Emigration, Landlords, and Tenants in Revolutionary Paris / Hannah Callaway -- 4. Home Fronts and Battlefields: The Army, Warfare, and the Revolutionary Experience / Christopher Tozzi -- 5. Race, Freedom, and Everyday Life: French Caribbean Prisoners of War in Britain / Abigail Coppins and Jennifer Ngaire Heuer -- Part 2: The Right To? - Revolutionary Justice at Work : 6. Crime, Law, and Justice / Claire Cage -- 7. Surveillance at Work: A Theft on the Rue du Bac / Ralph Kingston -- 8. Sex as Work: Public Women in Revolutionary Paris / Clyde Plumauzille -- 9. Doctors, Radicalism, and the Right to Health: Three Visions from the French Revolution / Sean M. Quinlan -- Part 3: Revolutionary Experiences, Practices, Sensations : 10. Tasting Liberty: Food and Revolution / E. C. Spary -- 11. Spectacles of French Revolutionary Violence in the Atlantic World / Ashli White -- 12. Practice and Belief: Religion in the Revolution / Jonathan Smyth -- 13. Facing the Unknown: The Private Lives of Miniatures in the French Revolutionary Prison / Sophie Matthiesson -- 14. Revolutionary Parents and Children: Everyday Lives in Times of Stress / Siân Reynolds.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: European history; France -- Social life and customs -- 1789-1815.; France -- History -- Revolution, 1789-1799 -- Influence; France -- History -- Revolution, 1789-1799 -- Social aspects; France -- Social conditions -- 18th century; Electronic books